Legal Certainty in the Re-Norming of Article 66(1) of the Notary Law - Izza Safira; M. Hamidi Masykur; Letiza Dessy Andreassari (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2027)
This study aims to evaluate the consistency of legal certainty and the constitutional implications resulting from the re-norming of the phrase "with the approval of the Notary Honorary Council" in Article 66 paragraph (1) of Law Number 2 of 2014 concerning the Amendment to the Notary Office Law. It specifically addresses whether reviving a mechanism previously declared unconstitutional under a renamed institution fulfills the constitutional guarantees of legal certainty and assesses it s wider legal impacts on the national law enforcement process involving notary public officials This research employs a normative legal research method (library research) focusing on the analysis of documented legal materials. The study utilizes a statutory approach and a conceptual approach, heavily grounded in the constitutional doctrines of judicial independence, equality before the law, and the classic theories of legal certainty developed by Hans Kelsen and Jan Michiel Otto. The primary legal materials examined include the 1945 Constitution, relevant notary position laws, and the Constitutional Court Decision Number 49/PUU-X/2012. The results indicate that, from the perspective of Jan Michiel Otto’s theory of real legal certainty, the re-norming fails to establish just legal certainty due to severe normative inconsistencies, an absence of academic justification in legislative drafts, and a lack of parliamentary compliance toward final and binding judicial reviews. Juridically, by shifting extra-judicial administrative approval from the Regional Supervisory Council (MPD) to the Notary Honorary Council (MKN), the provision establishes a severe norm conflict that overrides standard criminal procedural mandates (KUHAP) and compromises judicial independence. Sociologically, empirical evidence demonstrates that this gatekeeping function operates as an aggressive institutional filter rather than an objective protection of confidentiality, significantly obstructing material truth-seeking, delaying judicial due process, and leading to high operational case termination rates by law enforcement agencies.